REGARDING THE PHOTO FROM DOROTHEA LANGE ON MIGRANT MOTHER - Uğur GÜNAY YAVUZ (Fırat University, 2019)
Photos have been taken for various reasons, since it was invented in 1827. These photos, taken for various reasons, have been increasingly used for various occasions, after the photography spread day by day in our daily life and its great effect on people was realised. In this respect, Dorothea Lange’s photo, named “Migrant Mother” and taken in California, USA in 1936, became a photo that has been used and interpretted by both professional and amateur artists; or even by anyone who are competent in computer programs, but fine arts. Computers became an integral part of our lives; consequently the number of social and photo sharing sites have been increasing and they are used by increasing number of people. They use this specific “Migrant Mother” photo with their subjective comments on their pages and profiles or re-take the photo and share with their followers. Besides, this photo has turned into an advertisement and propoganda material by people, who realised its effect and power. Remarkably, it has been applied on various materials for commercial business and created a giftware business, such as t-shirts, ties, coffee cups, key-chains, bags and mobile cases. The aim of this art work is to express the photo’s power, its effect on people,